Development of Indonesian Gait Database using 2D optical motion analyzer system - Mahyuddin, Andi Isra; Mihradi, Sandro; Dirgantara, Tatacipta; Moeliono, Marina; Prabowo, Tertianto (ASEAN engineering journal)
This paper presents a review on the development of affordable optical based gait analysis systems at Institut Teknologi Bandung. The development started with a 2D inverse dynamic analysis of human gait using five linkages based on an experimental motion data. Using a simple system consist of a camera, LED markers and a PC, the position of the markers were obtained by capturing and processing digital images of markers attached to human body during motion. The marker positions data was then used for further kinematics and dynamic analyses. An in-house kinematic and kinetic software has been developed for this purpose. From the analyses, the spatio temporal gait parameters such as stride-length, cadence, cycle-time, speed and joint angles can be obtained as well as forces and moments. In the second stage, the 2-D analysis was improved by using seven linkages to include the foot. Using this, the system has been able to analyze ankle angle, position of the centre of pressure and ground reaction force distribution. Currently, the development is continued further for a 3D dynamic analysis of human gait using two cameras and a PC. As an outcome of this development, a database of Indonesian normal gait was established. This result is the first data available for gait of Indonesian. It is hoped that the quantitative data provided by this system can help physicians to diagnose and plan the treatment for patients.